The quick and the dead - Moore, Simon, 1958-; Donen, Joshua; Shapiro, Allen; Markey, Patrick; Raimi, Sam.; Stone, Sharon, 1958-; Hackman, Gene.; DiCaprio, Leonardo; Tri-Star Pictures; Japan Satellite Broadcasting, Inc.; Indieprod (Firm); Columbia TriStar Home Video (Firm) (Culver City, Calif. : Columbia TriStar Home Video, 2000)
This reinvention of the American Western is a wild, sexy shoot-out studded with action, suspense and offbeat humor.
Side A. Widescreen (1.85:1 aspect ratio) -- Side B. Full screen (1.33:1 aspect ratio).
DVD release of the 1995 motion picture.
Special features: scene selections; theatrical trailer.
Director of photography, Dante Spinotti ; editor, Pietro Scalia ; music, Alan Silvestri.
Sharon Stone, Gene Hackman, Russell Crowe, Roberts Blossom, Kevin Conway, Lance Henriksen, Pat Hingle, Gary Sinise, Leonardo DiCaprio.
DVD; English (Dolby digital 5.1), English (Dolby digital 2.0 surround), French (Dolby digital 2.0 mono).
English or French with optional English or French subtitles.
Keywords: Revenge -- Drama; Young women -- Drama; West (U.S.) -- Drama; Western films